UJI AKTIVITAS KITIN DEASETILASE ISOLAT BAKTERI DARI KAWASAN GEOTERMAL DIENG - Ghaida Afra Akhsani; Agung Suprihadi; Sri pujiyanto (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Chitinolytic bacteria is a bacterium, which is able to degrade chitin. This ability is obtained from the resulted chitinolytic enzyme. Chitin deacetylase (EC 3.5.1.41) is one of the chitinolytic enzymes, which be able to convert chitin into its derivatives. For this reason, chitin deacetylase has a chance to be an environmentally enzymatic converter of chitin. In addition, chitin derivatives have a wider potential in many fields. The objectives of this study were to obtain bacterial isolates from the mud of Sikidang Crater in Dieng geothermal field that producing chitin deacetylase enzyme, and to determine its activity characteristic of (optimum time production, optimum pH, and effect of 1 mM divalent metal ions) from the resulted chitin deacetylase enzyme. This research used completely randomized design. The data were analyzed using One Way ANOVA and Tukey HSD test. The results showed that KSR HA 24 isolates were able to produce chitin deasetylase with optimum enzyme activity of 0.668 U / ml at 18 hours production time. Optimum activity of chitin deacetylase occurred at pH 5 of 0.75 U / ml. Chitin deacetylase activity with 1 mM addition of divalent metal ions produce activator metal ions, including Mg2+, which increased the activity up to 154.43%, Fe2+ the activity up to 144.63%, and Cu2+ the activity up to 110.41%. Inhibitor metal ions, including Zn2+, which decreased the activity to 93.77%, and Mn2+ the activity to 86.46%.Keywords: Chitinolytic, Chitin Deacetylase, Enzyme Activity, pH, Divalent Metal Ions